Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kreatif Peserta Didik SMA - Agustina Elizabeth; Maria Magdalena Sigahitong (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
Has be done research about the effect of Problem Based Learning model on students’ creative thinking abilityin SMAS Katolik St. John Paul II maumere. This type of research is a quasi experiment with the Nonequivalent Control Group Design. Sampling is done by nonprobability sampling technique, (class XI MIA 1 and class XI MIA), which is satueated sampling where all populations are sampled. The creative thinking ability of students in this study were collected with creative thinking ability test in the form of essay test consisted 10 items and observation sheets. The result showed that : 1) the average score of creative thinking ability from students who take learning using Problem Based Learning model are 73.80; 2) the average score of creative thinking ability from students who take learning with Expository Learning model are 65.97; 3) there are differences in creative thinking ability significantly between students who learn to use the Problem Based Learning model with students who learn to use Expository Learning model. Students who learned Problem Based Learning model show better think creative than who learned Expository Learning model. Thus, Proble, Based Learning model influences students creative thinking abilities.